Negative electrode active material for secondary battery and secondary battery

By using silicate composite particles including crystalline silicon particles, amorphous lithium silicate phase and silicon oxide phase as negative electrode active substances in secondary batteries, the stress problems caused by expansion and contraction of silicon particles are solved, and the stress problems are improved Charge and discharge cycle characteristics and capacity stability.

CN114902447BActive Publication Date: 2025-02-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080090406.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-26
Filing Date
2020-10-15
Publication Date
2025-02-21
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

In the existing secondary batteries, the negative electrode active substance containing silicon increases stress due to the expansion and contraction of silicon particles during the charging and discharging process, resulting in cracks and cracks of composite particles, reducing the charge and discharge cycle characteristics.

Method used

Silicate composite particles are used as the negative electrode active material, which contains crystalline silicon particles, amorphous lithium silicate phase and silicon oxide phase, and the silicon oxide phase is dispersed in the amorphous lithium silicate phase. Particles, alleviate the stress caused by expansion and contraction of silicon particles.

Benefits of technology

It effectively suppresses cracks and cracks of composite particles, improves the stability of charge and discharge cycle characteristics, and significantly reduces the reduction of irreversible capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114902447B_ABST
    Figure CN114902447B_ABST
Patent Text Reader

Abstract

A negative electrode active material for a secondary battery includes silicate composite particles including: crystalline silicon particles; an amorphous phase including Li, O, and Si elements; and a silicon oxide phase, wherein the silicon phase and the silicon particles are dispersed in the amorphous phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure mainly relates to the improvement of negative electrode active materials for secondary batteries. Background Art

[0002] In recent years, secondary batteries such as non-aqueous electrolyte secondary batteries have high voltage and high energy density, and are therefore expected to be used as power sources for small civilian applications, power storage devices, and electric vehicles. When high energy density of batteries is required, the use of materials including silicon that alloys with lithium as negative electrode active materials with high theoretical capacity density is expected.

[0003] However, the irreversible capacity of the material containing silicon is large, so there is a problem of low initial charge and discharge efficiency (especially the ratio of the initial discharge capacity to the initial charge capacity). Therefore, various techniques have been proposed, such as pre-introducing lithium equivalent to the irreversible capacity into the material containing silicon. Specifically, a method of using composite particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase has been proposed (Patent Document 1). Silicon particles contribute to the charge and discharge reaction (reversibly absorbing and releasing lithium).

[0004] The composite particles are produced, for example, by sintering a mixture of glassy lithium silicate powder and silicon particles in a high-temperature and high-pressure atmosphere. At this time, the lithium silicate phase has crystallinity, and a clear peak derived from the lithium silicate appears in the X-ray diffraction pattern.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-153520 Summary of the invention

[0008] It is known that when the above-mentioned composite particles are charged and discharged, the silicon particles expand and contract greatly due to the absorption and release of lithium. Therefore, as the silicon particles expand and contract, a large stress is generated in the lithium silicate phase existing around the silicon particles, and thus the composite particles will crack and crack. The bonding force between the composite particles and the surrounding adhesive materials is weakened, and in particular, the cracked composite particles will lose the conductive path with the surrounding particles and become isolated. In addition, the side reaction between the electrolyte and the silicon particles is promoted. As a result, the charge and discharge cycle characteristics are reduced.

[0009] One aspect of the present disclosure relates to a negative electrode active material for a secondary battery, comprising silicate composite particles, the silicate composite particles comprising: crystalline silicon particles; an amorphous phase comprising Li, O, and Si elements; and a silicon oxide phase, wherein the silicon oxide phase and the silicon particles are dispersed in the amorphous phase.

[0010] Another aspect of the present disclosure relates to a secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, wherein the negative electrode comprises a current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the negative electrode active material for the secondary battery.

[0011] By using the negative electrode active material disclosed herein, a secondary battery having excellent charge and discharge cycle characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Schematic cross-sectional view of a negative electrode active material (LSX particles) according to one embodiment of the present disclosure.

[0013] Figure 2 It is a partially cutaway perspective view of a secondary battery according to one embodiment of the present disclosure.

[0014] Figure 3 is a diagram showing an example of an XRD-based diffraction pattern of LSX particles. DETAILED DESCRIPTION

[0015] The negative electrode active material for a secondary battery of an embodiment of the present disclosure comprises silicate composite particles (hereinafter, also referred to as LSX particles), wherein the silicate composite particles include: crystalline silicon particles; an amorphous phase including Li element, O element, and Si element (hereinafter, also referred to as "amorphous lithium silicate phase" or simply "lithium silicate phase"); and a silicon oxide phase. By using such a negative electrode active material, the stress accompanying the expansion and contraction of the silicon particles is alleviated by the amorphous lithium silicate phase, and the cracking and cracking of the composite particles can be suppressed. Therefore, the reduction in charge and discharge cycle characteristics is suppressed.

[0016] In LSX particles, multiple primary particles containing lithium silicate phases and silicon particles are combined to form secondary particles. From the perspective of the secondary particles as a whole, LSX particles have an island structure in which silicon particles as islands are dispersed in the lithium silicate phase as a sea. By controlling the amount of silicon particles dispersed in the lithium silicate phase, high capacity can be achieved, and the silicon particles are dispersed in the lithium silicate phase, so it is easy to suppress the expansion and contraction of the LSX particles during charging and discharging. Furthermore, the lithium silicate phase is amorphous, which can significantly suppress the expansion and contraction of the LSX particles. Therefore, it is easy to take into account both the high capacity of the battery and the improvement of the cycle characteristics.

[0017] In the past, composite particles were produced by mixing lithium silicate powder and silicon particles, crushing the mixture with a ball mill or the like to compound it, and sintering the crushed mixture in a high-temperature and high-pressure atmosphere. Amorphous lithium silicate powder can be used, or crystalline lithium silicate powder can be used. However, even when crystalline lithium silicate powder is used, the crystalline lithium silicate will change to amorphous by adding shear force based on stirring the mixture. By sintering at high temperature, the crystallinity of the lithium silicate will be restored, and composite particles with silicon particles dispersed in the crystalline lithium silicate phase can be obtained.

[0018] In this regard, in the present embodiment, composite particles are formed without sintering at a high temperature. If necessary, heat treatment and / or pressure treatment may be performed at a relatively low temperature (for example, below 450°C) at which the lithium silicate does not crystallize. As a result, the crystal growth of the lithium silicate is suppressed, and LSX particles in which silicon particles are dispersed in an amorphous lithium silicate phase are obtained. In the LSX particles, the lithium silicate phase is amorphous, and thus the charge capacity in the initial charge and discharge tends to increase. Furthermore, since the softness is higher than that of the crystals, the amorphous phase is more, and therefore the lithium silicate phase can follow the expansion and contraction of silicon, and the frequency of the silicon particles being isolated and unable to be charged and discharged is reduced. As a result, the capacity reduction under the charge and discharge cycle after the first time is significantly suppressed. Therefore, considering multiple charge and discharge cycles, the LSX particles of the present embodiment are advantageous.

[0019] The particle size distribution of the lithium silicate powder is broadened by composite formation based on pulverization. As a result, the mixture after pulverization contains a large amount of lithium silicate fine powder with a small particle size. In the conventional method, such fine powder is integrated with the lithium silicate of the composite particles by sintering at high temperature and high pressure. In contrast, in the method of this embodiment in which sintering at high temperature and high pressure is not performed, the surface area of ​​the manufactured LSX particles may increase and the side reactions may increase. Therefore, it is preferred to classify the stirred mixture to remove the lithium silicate particles with a small particle size.

[0020] LSX particles are produced by crushing and compounding silicon and lithium silicate. When the lithium in lithium silicate decreases and the silicon oxide increases, silicon oxide is generated during the production process of lithium silicate. Although a large amount of silicon oxide becomes amorphous during the crushing process, crystallized silicon oxide will precipitate finely in the subsequent heating process. Crystallized silicon oxide is stable and does not react with lithium ions even during charging, does not cause irreversible reactions, and is fine, so it is not easy to hinder the expansion and contraction of silicon particles.

[0021] On the other hand, when there are many crystals of lithium silicates such as Li2Si2O5, the LSX particles will expand and shrink, which can easily cause cracks in the particles. In addition, for the lithium silicate phase, the amorphous softness is higher than the crystalline softness, so it is easy to follow the expansion and contraction of silicon particles. Therefore, by mixing the two phases of crystalline silicon oxide phase and amorphous lithium silicate phase, the stress accompanying the expansion and contraction of silicon particles can be further alleviated. In this way, a negative electrode active material with good cycle characteristics and small irreversible capacity can be achieved.

[0022] The silicon oxide phase may be dispersed in the amorphous lithium silicate phase in the LSX particles. In other words, the silicon oxide phase and the silicon particles may be dispersed in the amorphous lithium silicate phase.

[0023] In the diffraction pattern of the LSX particles of this embodiment based on the X-ray diffraction method (XRD), peaks originating from silicon particles and silicon oxide phases may appear. On the other hand, peaks originating from lithium silicates do not appear substantially. Specifically, near 2θ=28°, a peak originating from the Si(111) plane of silicon particles may appear. In addition, near 2θ=26°, a peak originating from the SiO2(011) plane of the silicon oxide phase may appear. The half-value width W1 of the peak originating from the Si(111) plane of silicon particles can be, for example, greater than 0.3 and less than 1.5. The half-value width W2 of the peak originating from the SiO2(011) plane of the silicon oxide phase can be, for example, greater than 0.2 and less than 0.6. It should be noted that the X-ray used in the XRD method can use the Kα line of Cu. In addition, the above-mentioned half-value widths W1 and W2 mean the half-value full width of the range whose values ​​show a value greater than half of the highest value in the peak.

[0024] Figure 3 Examples of XRD diffraction patterns of the LSX particles of the present embodiment and conventional LSX particles are shown. Figure 3 In the figure, the diffraction pattern of the LSX particle X3 shown by the solid line is the LSX particle of the present embodiment, and the diffraction pattern of the LSX particle Y3 shown by the dotted line is the LSX particle of the prior art. It should be noted that the LSX particle X3 corresponds to Example 3 (battery A3) in the examples described later, and the LSX particle Y3 corresponds to Comparative Example 3 (battery B3).

[0025] In LSX particles X3 and Y3, a peak originating from the Si(111) plane of silicon particles was observed near 2θ=28°. In addition, a peak originating from the SiO2(011) plane of the silicon oxide phase was observed near 2θ=26°. Furthermore, in LSX particle Y3, a peak originating from lithium silicate Li2Si2O5 was observed near 2θ=24°. On the other hand, in LSX particle X3, there was no peak near 2θ=24°. It should be noted that, although it was not observed in LSX particles X3 and Y3, a peak originating from lithium silicate Li2SiO3 may appear near 2θ=19°. The peak near 2θ=20° is a peak originating from SiO2.

[0026] In the XRD pattern, the peak originating from the Si(111) plane of the silicon particles is separated, and the integrated intensity obtained by integrating the separated peak within the range of 2θ=23° to 30° is set as I1. Similarly, the peak originating from the SiO2(011) plane of the silicon oxide phase is separated, and the integrated intensity obtained by integrating the separated peak within the range of 2θ=23° to 30° is set as I2. The sum of I1 and I2 is set as A. Furthermore, the total integrated intensity I in the range of 2θ=23° to 30° is set as total The integrated intensity obtained by removing the peaks derived from silicon particles and silicon oxide phases is set as B. The integrated intensity B may include the contribution of lithium silicate based on crystallinity. In this case, the ratio B / A of the integrated intensity B to the integrated intensity A may be 0.03 or less. In this case, the inhibitory effect of the reduction of the charge and discharge cycle characteristics is significant. The ratio B / A is 0.02 or less, or may be 0.01 or less.

[0027] In LSX particles, the amorphous lithium silicate phase contains, for example, the formula: Li 2z SiO 2+z The oxide phase represented by (0<z<1) is preferably z=1 / 2 from the viewpoints of stability, ease of production, lithium ion conductivity, etc.

[0028] The lithium silicate phase may contain other elements in addition to Li, Si, and O (oxygen). For example, the lithium silicate phase may contain at least one element selected from the group consisting of alkali metal elements (excluding Li) and Group II elements.

[0029] By making the lithium silicate phase contain alkali metal elements other than Li, it becomes difficult to crystallize, the viscosity of the molten state is reduced, and the fluidity is increased. Therefore, even in the heat treatment at a low temperature, it is easy to embed into the gaps between silicon particles, and it is easy to generate dense composite particles. Alkali metal elements are low in price, so they can be Na and / or K. The atomic ratio of the alkali element X (for example, K) other than Li contained in the lithium silicate phase relative to Li: X / Li can be, for example, 0.1 to 7.1, can be greater than 0.4 and less than 5, or can be greater than 0.7 and less than 2.

[0030] The lithium silicate phase may also contain Group II elements. Generally, the silicate phase is alkaline, but the Group II elements have the effect of inhibiting the dissolution of alkali metals from the silicate phase. Therefore, when preparing a slurry containing a negative electrode active material, the slurry viscosity is easily stabilized. Therefore, the necessity of treatment (such as acid treatment) for neutralizing the alkaline component of the LSX particles is also reduced.

[0031] As the Group II element, at least one selected from the group consisting of Be, Mg, Ca, Sr, Ba and Ra can be used. Among them, Ca is preferred from the perspective of being able to improve the Vickers hardness of the lithium silicate phase and further improve the cycle characteristics. The content of the Group II element is, for example, 20 mol% or less, 15 mol% or less, or 10 mol% or less relative to the total amount of elements other than O contained in the lithium silicate phase.

[0032] The lithium silicate phase may also contain other elements M in addition to alkali metal elements and Group II elements. The element M may be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W. Specifically, for example, B has a low melting point, which is beneficial for improving fluidity during sintering. Although Ca reduces ion conductivity, it has the effect of increasing the hardness of the lithium silicate phase. Al, Zr, Nb, Ta and La can increase the hardness while maintaining ion conductivity. Relative to the total amount of elements other than O contained in the lithium silicate phase, the content of the element M is, for example, less than 10 mol%, and can be less than 5 mol%.

[0033] The contents of B, Na, K and Al contained in the lithium silicate phase were determined by quantitative analysis in accordance with JIS R3105 (1995) (Analysis method for borosilicate glass), and the Ca content was determined by quantitative analysis in accordance with JIS R3101 (1995) (Analysis method for soda-lime glass).

[0034] Other contained elements can be obtained by the following method. First, a sample of the lithium silicate phase or LSX particles containing it is completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid and sulfuric acid), and the carbon in the solution residue is filtered out. Thereafter, the obtained filtrate is analyzed by inductively coupled plasma emission spectrometry (ICP-AES) to measure the spectral intensity of each element. Then, a standard curve is prepared using a commercially available standard solution of the element, and the content of each element contained in the lithium silicate phase is calculated.

[0035] In the silicate composite particles, there are lithium silicate phase, silica phase, and silicon particles, and they can be distinguished and quantified by using Si-NMR. As described above, the Si content obtained by ICP-AES is the total of the Si amount constituting the silicon particles, the Si amount in the lithium silicate phase, and the Si amount in the silica phase. On the other hand, the Si amount constituting the silicon particles can also be quantified by using Si-NMR. Therefore, by subtracting the Si amount constituting the silicon particles and the Si amount in the silica phase from the Si content obtained by ICP-AES, the Si amount in the lithium silicate phase can be quantified. It should be noted that as the reference material necessary for quantification, a mixture containing a silicate phase and silicon particles in a specified ratio with a known Si content can be used.

[0036] Hereinafter, the measurement conditions of the desired Si-NMR are shown.

[0037] <Si-NMR Measurement Conditions>

[0038] Measuring device: Solid nuclear magnetic resonance spectrometer (INOVA-400) manufactured by Varian, Inc.

[0039] Probe: Varian 7mm CPMAS-2

[0040] MAS: 4.2 kHz

[0041] MAS speed: 4 kHz

[0042] Pulse: DD (45° pulse + signal acquisition time 1H decoupling)

[0043] Repetition time: 1200 seconds to 3000 seconds

[0044] Observation width: 100 kHz

[0045] Observation center: Around -100 ppm

[0046] Signal acquisition time: 0.05 seconds

[0047] Number of accumulations: 560

[0048] Sample amount: 207.6 mg

[0049] In order to improve the high-capacity and cycle characteristics, the content of silicon particles in the LSX particles may be, for example, 30% by mass or more and 80% by mass or less. By setting the content of silicon particles to 30% by mass or more, the proportion of the lithium silicate phase becomes smaller, and it becomes easier to improve the initial charge-discharge efficiency. By setting the content of silicon particles to 80% by mass or less, it becomes easier to reduce the degree of expansion and contraction of the LSX particles during charge and discharge.

[0050] The silicon particles dispersed in the lithium silicate phase have a granular phase of silicon (Si) single substance, and are composed of a single or multiple crystallites. The crystallite size of the silicon particles is preferably less than 30nm. When the crystallite size of the silicon particles is less than 30nm, the volume change caused by the expansion and contraction of the silicon particles accompanying charging and discharging can be reduced, and the cycle characteristics are further improved. For example, when the silicon particles shrink, gaps are formed around the silicon particles, and the contact points between the particles and the surroundings are reduced, thereby suppressing the isolation of the particles, and suppressing the reduction in charge and discharge efficiency caused by the isolation of the particles. The lower limit of the crystallite size of the silicon particles is not particularly limited, for example, it is 5nm.

[0051] The crystallite size of the silicon particles is more preferably 2 nm or more and 30 nm or less, and more preferably 2 nm or more and 20 nm or less. When the crystallite size of the silicon particles is less than 20 nm, the expansion and contraction of the silicon particles can be uniformized, and the fine cracks of the particles caused by the expansion and contraction of the silicon particles during charge and discharge can be reduced, thereby improving the cycle characteristics. The crystallite size of the silicon particles can be calculated using the Scherrer formula based on the half-value width of the diffraction peak of the Si (111) surface belonging to the X-ray diffraction (XRD) pattern of the silicon particles.

[0052] At least a portion of the surface of the LSX particles may also be covered with a conductive material. The lithium silicate phase lacks electronic conductivity, so the conductivity of the LSX particles also tends to decrease. However, by covering the surface of the secondary particles of the lithium silicate phase with a conductive material and forming a conductive layer, the conductivity of the LSX particles can be greatly improved. As the conductive material, a carbon material is preferred. The carbon material preferably includes at least one selected from the group consisting of a carbon compound and a carbonaceous material.

[0053] The thickness of the conductive layer is preferably not substantially affected by the average particle size of the LSX particles. In order to ensure conductivity and the diffusibility of lithium ions, the thickness of the conductive layer is preferably 1 to 200 nm, more preferably 5 to 100 nm. The thickness of the conductive layer can be measured by cross-sectional observation of the LSX particles using a SEM or TEM (transmission electron microscope).

[0054] As carbon compounds, for example, compounds containing carbon and hydrogen, compounds containing carbon, hydrogen and oxygen can be mentioned. As carbonaceous materials, amorphous carbon with low crystallinity, graphite with high crystallinity, etc. can be used. As amorphous carbon, carbon black, carbonaceous stone, coke, charcoal, activated carbon, etc. can be mentioned. As graphite, natural graphite, artificial graphite, graphitized mesophase carbon particles, etc. can be mentioned. Among them, amorphous carbon is preferred from the perspective of low hardness and strong buffering effect on silicon particles undergoing volume change during charge and discharge. Amorphous carbon can be easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). As carbon black, acetylene black, Ketjen black, etc. can be mentioned.

[0055] The LSX particles can be removed from the battery by the following method. First, disassemble the battery and remove the negative electrode. Wash the negative electrode with anhydrous ethyl methyl carbonate or dimethyl carbonate to remove the electrolyte. Then, peel the negative electrode mixture from the copper foil and crush it with a mortar to obtain a sample powder. Next, dry the sample powder in a dry atmosphere for 1 hour, immerse it in gently boiling 6M hydrochloric acid for 10 minutes to remove alkali metals such as Na and Li that may be contained in the binder, etc. Then, wash the sample powder with ion-exchanged water and filter it, and dry it at 200 °C for 1 hour. After that, heat it to 900 °C in an oxygen atmosphere to remove the carbon component, and thus only the LSX particles can be separated.

[0056] The cross-sectional observation of the LSX particles can be carried out, for example, by the following method. First, disassemble the battery and take out the negative electrode. Use a cross-section polisher (CP) to obtain the cross-section of the negative electrode mixture layer. Observe the cross-section of the negative electrode mixture layer with a scanning electron microscope (SEM). From the cross-sectional image of the backscattered electron image of the negative electrode mixture layer, randomly select 10 LSX particles with a maximum diameter of 5 μm or more, and perform mapping analysis of an element (for example, carbon) based on energy-dispersive X-ray (EDX) for each of them. Use image analysis software to calculate the area occupied by the target element. The ideal observation magnification is 2000 - 20000 times. Calculate the average of the measured values of the area occupied by the specified element of the 10 obtained particles.

[0057] It should be noted that during the charge and discharge process, a coating film is formed on the surface of the LSX particles through the decomposition of the electrolyte, etc. In addition, as described later, the LSX particles sometimes also have a conductive layer covering the surface of the composite particles. Therefore, in the mapping analysis based on EDX, it is carried out for the range 1 μm inside from the peripheral edge of the cross-section of the LSX particles in such a way that the thin coating film and the conductive layer are not included in the measurement range. Through the mapping analysis based on EDX, the distribution state of the carbon material inside the LSX particles can also be confirmed. It is difficult to distinguish the decomposition products of the electrolyte at the end of the cycle, so it is preferable to measure the samples before or at the beginning of the cycle.

[0058] The following shows the measurement conditions for the desired cross-sectional SEM-EDX analysis.

[0059] <SEM-EDX measurement conditions>

[0060] Processing device: manufactured by JEOL, SM-09010 (Cross Section Polisher)

[0061] Processing conditions: acceleration voltage 6 kV

[0062] Current value: 140 μA

[0063] Vacuum degree: 1×10 -3 ~2×10-3 Pa

[0064] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0065] Accelerating voltage during analysis: 10kV

[0066] Field: Free Mode

[0067] Probe current: Medium

[0068] Probe current range: High

[0069] Anode Ap.: 3

[0070] OBJ Ap.:2

[0071] Analysis area: 1μm square

[0072] Analysis software: EDAX Genesis

[0073] CPS: 20500

[0074] Lsec: 50

[0075] Time constant: 3.2

[0076] In addition, in addition to SEM-EDX analysis, Auger electron spectroscopy (AES), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc. can also be used to quantify each element in the silicate composite particles contained in the negative electrode active material layer in the discharged state.

[0077] Next, the method for producing LSX particles will be described in detail.

[0078] Process (i)

[0079] The raw material of lithium silicate uses a raw material mixture containing a raw material containing Si and a Li raw material in a specified ratio. The raw material mixture may also contain the above-mentioned alkali metal elements, Group II elements, and / or element M. The mixture mixed with a specified amount of the above-mentioned raw materials is melted, and the melt is sheeted by a metal roller to produce lithium silicate. Afterwards, the sheeted silicate is heat-treated in an atmospheric atmosphere at a temperature above the glass transition point and below the melting point to crystallize it. It should be noted that the sheeted silicate can also be used without crystallizing it. In addition, it is also possible to manufacture silicate by solid phase reaction without melting the mixture mixed in a specified amount, but sintering it at a temperature below the melting point.

[0080] Silicon oxide can be used as the Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as the Li raw material. These can be used alone or in combination of two or more. The raw materials of alkali metal elements, Group II elements, and element M can include oxides, hydroxides, carbonate compounds, hydrides, nitrates, sulfates, etc. of each element.

[0081] The Si raw material that does not react with the Li raw material may remain in the lithium silicate. The remaining Si raw material is dispersed in the lithium silicate in the form of a silicon oxide phase.

[0082] Step (ii)

[0083] Next, raw material silicon is mixed with lithium silicate to form a composite. For example, composite particles are produced through the following steps (a) to (c).

[0084] Process (a)

[0085] First, raw silicon powder and lithium silicate powder are mixed at a mass ratio of 20:80 to 95:5, for example. Coarse silicon particles having an average particle size of several to several tens of μm may be used as the raw silicon.

[0086] Process (b)

[0087] Next, a pulverizing device such as a ball mill is used to pulverize and compound the mixture of raw silicon and lithium silicate while micronizing the mixture. At this time, an organic solvent may be added to the mixture to perform wet pulverization. A predetermined amount of organic solvent may be added to the pulverizing container at once at the beginning of pulverization, or may be added to the pulverizing container several times and intermittently during the pulverization process. The organic solvent serves to prevent the pulverized object from adhering to the inner wall of the pulverizing container.

[0088] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide or the like can be used.

[0089] It should be noted that the raw silicon and lithium silicate may be micronized and then mixed. In addition, silicon nanoparticles and amorphous lithium silicate nanoparticles may be prepared without using a pulverizing device and then mixed. The nanoparticles may be prepared using a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0090] Process (c)

[0091] Next, the micronized mixture is classified to remove components with small particle sizes. By classification, for example, particles of lithium silicate with a particle size of less than 0.5 μm can be removed. The classifier used for classification is not particularly limited as long as it can classify particles with a particle size of less than 0.5 μm. However, classification is usually performed by placing the particles in a fluid flow, causing a force (for example, inertial force or centrifugal force) to act on the particles with the help of the fluid, and utilizing the difference between the forces acting on particles of different particle sizes. Therefore, the reactivity of the fluid (gas or liquid) used for classification with lithium silicate must be low. From this point of view, a dry classifier using gas as a fluid is preferably used as a classifier. However, if a liquid with low reactivity with lithium silicate is used as a fluid, a wet classifier can also be used. The principle of classification of the classifier is not particularly limited, for example, inertial force can be utilized, and centrifugal force can also be utilized. An elbow jet classifier utilizing the wall effect can also be used.

[0092] Process (iii)

[0093] Next, at least a portion of the surface of the composite particles (secondary particles) can be covered with a conductive material to form a conductive layer. The conductive material is preferably electrochemically stable, and a conductive carbon material is preferably used. As a method for covering the surface of the composite particles with a conductive carbon material, there can be exemplified a CVD method using hydrocarbon gases such as acetylene and methane as raw materials, a method of mixing coal tar, petroleum asphalt, phenolic resin, etc. with composite particles, and heating them to carbonize them. In addition, carbon black can also be attached to the surface of the composite particles. The covering of the conductive carbon material can be obtained, for example, by heating a mixture of the removed particles and the conductive carbon material at 700°C to 950°C under an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.).

[0094] Step (iv)

[0095] A step of washing the composite particles (including the case where the surface has a conductive layer) with an acid may also be performed. For example, by washing the composite particles with an acidic aqueous solution, a trace amount of alkali components that may be generated when the raw silicon and the lithium silicate are combined and that exist on the surface of the composite particles can be dissolved and removed. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, or an aqueous solution of an organic acid such as citric acid, acetic acid, or the like can be used.

[0096] Figure 1 The cross section of an LSX particle 20 as an example of a negative electrode material is schematically shown.

[0097] The LSX particle 20 includes a mother particle 23 composed of secondary particles formed by agglomerating a plurality of primary particles 24. The mother particle 23 (primary particle 24) includes: an amorphous lithium silicate phase 21, silicon particles 22 dispersed in the lithium silicate phase 21, and a silicon oxide phase 28. The mother particle 23 has a sea island structure in which fine silicon particles are dispersed in a matrix of the lithium silicate phase 21. The surface of the mother particle 23 may be covered with a conductive layer 26.

[0098] The lithium silicate phase 21 and the silicon particles 22 are both composed of fine primary particles. A silicon oxide phase 28 may also be dispersed in the lithium silicate phase 21. The SiO2 content in the mother particle 23 measured by Si-NMR is preferably 30% by mass or less, and more preferably less than 7% by mass, for example.

[0099] The mother particle 23 may also contain a lithium silicate phase 21, silicon particles 22, a silicon oxide phase 28, and other components other than the carbon material. For example, from the viewpoint of improving the strength of the mother particle 23, it may contain a reinforcing material such as an oxide such as ZrO2 or a carbide in an amount less than 10% by weight relative to the mother particle 23.

[0100] The average particle size of the primary particles 24 is preferably 0.2 to 10 μm, more preferably 2 to 8 μm. This makes it easier to further alleviate the stress caused by the volume change of the silicon particles accompanying charge and discharge, and it is easier to obtain good cycle characteristics. In addition, the surface area of ​​the LSX particles becomes appropriate, so the capacity reduction caused by the side reaction with the electrolyte is also suppressed.

[0101] The average particle size of the primary particles 24 is measured by observing the cross section of the negative electrode material using a SEM. Specifically, it can be determined by taking the average diameter of a circle equivalent to the cross-sectional area of ​​any 100 primary particles 24 (a circle having the same area as the cross-sectional area of ​​the primary particles).

[0102] The average particle size of the silicon particles 22 is less than 500 nm before the initial charge, preferably less than 200 nm, and more preferably less than 50 nm. By performing such appropriate miniaturization on the silicon particles 22, the volume change during charge and discharge becomes smaller, and the structural stability is improved. In addition, the expansion and contraction of the silicon particles are uniform, and the particle cracks are suppressed, thereby improving the cycle characteristics. The average particle size of the silicon particles 22 is measured by observing the cross section of the negative electrode material using SEM or TEM. Specifically, it can be calculated by taking the average of the maximum diameters of any 100 silicon particles 22.

[0103] The secondary battery of the embodiment of the present disclosure comprises a positive electrode, a negative electrode, an electrolyte, and a separator sandwiched between the positive electrode and the negative electrode. The negative electrode comprises: a current collector, and a negative electrode active material layer containing the negative electrode active material for the secondary battery. The negative electrode, positive electrode, electrolyte, and separator of the secondary battery of the embodiment of the present disclosure are described below.

[0104] [negative electrode]

[0105] The negative electrode, for example, comprises a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed by applying a negative electrode slurry formed by dispersing a negative electrode mixture in a dispersion medium on the surface of the negative electrode current collector and drying it. The dried coating film can also be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0106] The negative electrode mixture contains the negative electrode active material for secondary batteries containing the above-mentioned LSX particles as an essential component as the negative electrode active material, and can contain a binder, a conductive agent, a thickener, etc. as optional components. The silicon particles in the LSX particles can absorb a large amount of lithium ions, thus contributing to the high capacity of the negative electrode.

[0107] The negative electrode active material may also include other active material materials that electrochemically absorb and release lithium ions. As other active material materials, for example, carbon-based active materials are preferred. The volume of LSX particles expands and contracts with charging and discharging, so when its ratio in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charging and discharging. On the other hand, by using LSX particles and carbon-based active materials in combination, the high capacity of silicon particles can be imparted to the negative electrode, and excellent cycle characteristics can be achieved. The ratio of LSX particles in the total of LSX particles and carbon-based active materials is, for example, preferably 0.5 to 15% by mass, and more preferably 1 to 5% by mass. As a result, it becomes easy to take into account both high capacity and improved cycle characteristics.

[0108] As carbon-based active materials, examples include graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon). Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material with a graphite-type crystal structure, including, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon-based active material may be used alone, or two or more may be used in combination.

[0109] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, mesh, punched sheet, etc.) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and 5 to 20 μm is more ideal.

[0110] As binders, fluororesins, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and its derivatives can be exemplified. These can be used alone or in combination of two or more. As conductive agents, carbon black, conductive fibers, carbon fluoride, organic conductive materials can be exemplified. These can be used alone or in combination of two or more. As thickeners, carboxymethyl cellulose (CMC), polyvinyl alcohol can be cited. These can be used alone or in combination of two or more.

[0111] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0112] [positive electrode]

[0113] The positive electrode, for example, comprises a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry formed by dispersing a positive electrode mixture in a dispersion medium on the surface of the positive electrode current collector and drying it. The dried coating film can also be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.

[0114] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as optional components.

[0115] As the positive electrode active material, a lithium composite metal oxide can be used. Examples of the lithium composite metal oxide include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn2- b M b O4, LiMePO4, Li2MePO4F. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≤a≤1.2, 0≤b≤0.9, and 2.0≤c≤2.3. It should be noted that the value a showing the molar ratio of lithium increases or decreases by charging and discharging.

[0116] As the binder and the conductive agent, the same ones as exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can also be used.

[0117] The shape and thickness of the positive electrode current collector can be selected according to the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0118] [Electrolytes]

[0119] The electrolyte includes a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may contain a known additive.

[0120] The solvent may be an aqueous solvent or a non-aqueous solvent. As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, etc. may be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. may be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. may be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. may be mentioned. The non-aqueous solvent may be used alone or in combination of two or more.

[0121] As the lithium salt, for example, lithium salts containing chloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated acid imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0122] [Separator]

[0123] Generally, it is ideal to insert a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, a polyolefin such as polypropylene, polyethylene, etc. can be used.

[0124] As an example of the structure of a secondary battery, an electrode group in which a positive electrode and a negative electrode are wound with a separator and an electrolyte is contained in an outer shell can be cited. Alternatively, an electrode group in other forms such as a stacked electrode group in which a positive electrode and a negative electrode are stacked with a separator can be used instead of a wound electrode group. The secondary battery can be any type such as a cylindrical type, a square type, a coin type, a button type, a layer frame type, etc.

[0125] Figure 2 It is a partially cutaway perspective view of a square secondary battery according to one embodiment of the present disclosure.

[0126] The battery comprises a square-bottomed battery case 4, an electrode group 1 and an electrolyte contained in the battery case 4, and a sealing plate 5 for sealing the opening of the battery case 4. The electrode group 1 comprises a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween. The negative electrode, the positive electrode, and the separator are wound around a flat winding core, and the winding core is removed to form the electrode group 1. The sealing plate 5 comprises a liquid injection port blocked by a sealing plug 8, and a negative terminal 6 insulated from the sealing plate 5 by a gasket 7.

[0127] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to the sealing plate 5. A resin frame is arranged on the upper part of the electrode group 1 to separate the electrode group 1 from the sealing plate 5 and to separate the negative electrode lead 3 from the battery case 4.

[0128] <Example>

[0129] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0130] <Example 1>

[0131] [Preparation of LSX particles]

[0132] Process (i)

[0133] Lithium carbonate and silicon dioxide were mixed in a molar ratio of Li2CO3:SiO2=34:66, and the mixture was melted at 1500°C for 5 hours in an inert atmosphere, and the melt was passed through a metal roller to form a sheet, and then heat-treated at 750°C for 5 hours to obtain a lithium silicate composite oxide in the form of an amorphous and crystalline mixed phase. The obtained lithium silicate composite oxide was pulverized in such a way that the average particle size was 10 μm.

[0134] Step (ii)

[0135] A lithium silicate composite oxide with an average particle size of 10 μm and raw silicon (3N, average particle size of 10 μm) were mixed at a mass ratio of 70:30. The mixture was filled in a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was pulverized at 200 rpm for 25 hours in an inert atmosphere.

[0136] Next, the mixture was classified using an elbow jet classifier to remove fine particles with a particle size of less than 0.5 μm.

[0137] After that, the classified mixture was mixed with coal tar pitch (MCP250 manufactured by JFE Chemical Industry Co., Ltd.), and the mixture was calcined at 800° C. for 5 hours in an inert gas atmosphere to cover the surface of the LSX particles with conductive carbon and form a conductive layer. The covering amount of the conductive layer was set to 5% by mass relative to the total mass of the LSX particles and the conductive layer. After that, a sieve was used to obtain LSX particles (secondary particles) having an average particle size of 5 μm with a conductive layer. XRD analysis was performed on the LSX particles to determine whether there were peaks derived from Si, SiO2, Li2Si2O5, and Li2SiO3.

[0138] [Production of negative electrode]

[0139] LSX particles and graphite were mixed at a mass ratio of 5:95 to serve as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), styrene-butadiene copolymer rubber (SBR), and lithium polyacrylate were mixed at a mass ratio of 96.5:1:1.5:1, and after adding water, a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) was used to stir and prepare the negative electrode slurry. 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture on the surface of the copper foil would be 190 g, and the coating was dried and then rolled to form a copper foil with a density of 1.5 g / cm 3 The negative electrode of the negative electrode mixture layer.

[0140] [Production of positive electrode]

[0141] Lithium cobalt oxide, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and then stirred using a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of the aluminum foil, and the coating was dried and then rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.

[0142] [Preparation of electrolyte]

[0143] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and dimethyl carbonate (DEC) in a volume ratio of 3:7.

[0144] [Manufacturing of Secondary Batteries]

[0145] The electrode group was prepared by installing a tab on each electrode, and the positive electrode and the negative electrode were wound into a spiral shape with the tab located at the outermost periphery by means of a separator. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105°C for 2 hours, and then injected with a non-aqueous electrolyte, and the opening of the outer casing was sealed to obtain a secondary battery A1.

[0146] <Example 2>

[0147] In step (i), the mixing ratio of lithium carbonate and silicon dioxide is changed to a molar ratio of Li2CO3:SiO2=27:73.

[0148] LSX particles were prepared in the same manner as in Example 1 except for the above, and a negative electrode including the LSX particles was produced to obtain a secondary battery A2.

[0149] <Example 3>

[0150] In process (i), a mixture of lithium carbonate (Li2CO3), silicon dioxide (SiO2), calcium carbonate (CaCO3) and magnesium carbonate (MgCO3), and a mixture of boric acid (H3BO3), aluminum hydroxide (Al2(OH)3) and lanthanum oxide (La2O3) are mixed in a molar ratio of 20:70:2:8, and the mixture is melted at 1500°C in an inert atmosphere for 5 hours. The melt is made into sheets by passing through metal rollers, and is heat treated at 750°C for 5 hours to obtain a lithium silicate composite oxide in the form of a mixed phase of amorphous and crystalline phases.

[0151] LSX particles were prepared in the same manner as in Example 1 except for the above, and a negative electrode including the LSX particles was produced to obtain a secondary battery A3.

[0152] <Comparative Example 1>

[0153] In Example 1, the mixing ratio of lithium carbonate and silicon dioxide in step (i) was changed to a molar ratio of Li2CO3:SiO2=50:50.

[0154] The pulverized mixture in step (ii) was not classified, but was calcined at 600° C. for 4 hours in an inert atmosphere while applying pressure by hot pressing to obtain a sintered body of the mixture.

[0155] Then, the sintered body was crushed, passed through a 40 μm sieve, and mixed with coal tar (MCP250 manufactured by JFE Chemical Industry Co., Ltd.), and the mixture was fired at 800° C. for 5 hours in an inert atmosphere to cover the surface of the LSX particles with conductive carbon and form a conductive layer. The coating amount of the conductive layer was set to 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, a sieve was used to obtain LSX particles (secondary particles) having an average particle size of 5 μm with a conductive layer.

[0156] Using the above-mentioned LSX particles, a negative electrode was produced in the same manner as in Example 1 to obtain a secondary battery B1.

[0157] <Comparative Example 2>

[0158] In Comparative Example 1, the mixing ratio of lithium carbonate and silicon dioxide in step (i) was changed to a molar ratio of Li2CO3:SiO2=34:66.

[0159] LSX particles were prepared in the same manner as in Comparative Example 1 except for the above, and a negative electrode including the LSX particles was produced to obtain a secondary battery B2.

[0160] <Comparative Example 3>

[0161] In process (i), a mixture of lithium carbonate (Li2CO3), silicon dioxide (SiO2), calcium carbonate (CaCO3) and magnesium carbonate (MgCO3), and a mixture of boric acid (H3BO3), aluminum hydroxide (Al2(OH)3) and lanthanum oxide (La2O3) are mixed in a molar ratio of 20:70:2:8, and the mixture is melted at 1500°C for 5 hours in an inert atmosphere. The melt is made into sheets by passing through a metal roller, and is heat treated at 750°C for 5 hours to obtain a lithium silicate composite oxide in the form of a mixed phase of amorphous and crystalline phases.

[0162] LSX particles were prepared in the same manner as in Comparative Example 1 except for the above, and a negative electrode including the LSX particles was produced to obtain a secondary battery B3.

[0163] The following evaluations were performed on each battery of the examples and comparative examples.

[0164] [Initial discharge capacity]

[0165] Each battery was charged at 25°C at a constant current of 1 It (800 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA). After a 10-minute pause, the battery was discharged at a constant current of 1 It (800 mA) until the voltage reached 2.75 V, and the discharge capacity was evaluated. The discharge capacity of Example 1 was set to 100, and the others were standardized.

[0166] [Charge and discharge cycle test]

[0167] The charge and discharge were repeated under the following conditions.

[0168] <Charging>

[0169] At 25° C., constant current charging was performed at a current of 1 It (800 mA) until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 It (40 mA).

[0170] <Discharge>

[0171] At 25° C., constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V.

[0172] The pause period between charge and discharge was set to 10 minutes. The ratio of the discharge capacity of the 100th cycle to the discharge capacity of the 1st cycle was taken as the cycle maintenance rate, and the cycle maintenance rate of Example 1 was set to 100, and the others were standardized. If the cycle maintenance rate was 90 or more, the charge and discharge cycle characteristics were judged to be good.

[0173] The evaluation results of each battery A1 to A3, B1 to B3 are shown in Table 1. It should be noted that Table 1 summarizes the presence or absence of a peak derived from the Si (111) plane, a peak derived from the (011) plane of SiO2, a peak derived from lithium silicate (Li2Si2O5, Li2SiO3), and the half-value width (° / 2θ) of each peak by performing XRD analysis on the LSX particles used as the negative electrode active material of each battery. In addition, Table 1 also shows the ratio B / A of the above-mentioned integrated intensity in the LSX particles used as the negative electrode active material of each battery.

[0174] [Table 1]

[0175]

[0176] According to Table 1, the lithium silicate phase in the LSX particles exists in an amorphous state. Batteries A1 to A3 that do not have peaks originating from Li2Si2O5 and Li2SiO3 can obtain higher initial discharge capacity and cycle retention rate compared to batteries B1 to B3 that have a crystalline lithium silicate phase.

[0177] Industrial Applicability

[0178] The present disclosure can provide a nonaqueous electrolyte secondary battery having high capacity and good charge-discharge cycle characteristics. The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0179] Description of Reference Numerals

[0180] 1 Electrode set

[0181] 2 Positive lead

[0182] 3 Negative lead

[0183] 4 Battery housing

[0184] 5 Sealing plate

[0185] 6 Negative terminal

[0186] 7 Gasket

[0187] 8 seal

[0188] 20 LSX particles

[0189] 21 Lithium silicate phase

[0190] 22 Silicon particles

[0191] 23 Masterbatch

[0192] 24 primary particles

[0193] 26 Conductive layer

[0194] 28 Silica phase

Claims

1. A negative electrode active material for a secondary battery, comprising silicate composite particles, wherein the silicate composite particles include: crystalline silicon particles; an amorphous phase including Li element, O element, and Si element; and a crystalline silicon oxide phase, The silicon oxide phase and the silicon particles are dispersed in the amorphous phase. In a diffraction pattern based on an X-ray diffraction method XRD, the integration range is set to 23°~30°, and the ratio B / A of the total integrated intensity B excluding the peak originating from the Si (111) surface of the silicon particles and the peak originating from the SiO2 (011) surface of the silicon oxide phase from the total integrated intensity within the range of 2θ=23°~30°, to the integrated intensity I1 of the peak originating from the Si (111) surface of the silicon particles appearing in the range of 2θ=27°~30° and the integrated intensity I2 of the peak originating from the SiO2 (011) surface of the silicon oxide phase appearing in the range of 2θ=25°~27°, is less than 0.

03.

2. The negative electrode active material for a secondary battery according to claim 1, wherein In a diffraction pattern obtained by X-ray diffraction (XRD), a half-value width W1 of a diffraction peak derived from Si (111) plane of the silicon particles near 2θ=28° is 0.3 or more and 1.5 or less.

3. The negative electrode active material for a secondary battery according to claim 1, wherein In a diffraction pattern obtained by X-ray diffraction method XRD, a half-value width W2 of a diffraction peak derived from SiO 2 (011) plane of the silicon oxide phase near 2θ=26° is greater than or equal to 0.2 and less than or equal to 0.

6.

4. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The diffraction pattern by X-ray diffraction method XRD does not have a peak derived from lithium silicate.

5. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The amorphous phase further includes at least one element selected from the group consisting of alkali metal elements excluding Li and Group IIA elements.

6. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The amorphous phase further comprises an element M, The element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

7. A secondary battery comprising: a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, The negative electrode comprises a current collector and a negative electrode active material layer. The negative electrode active material layer contains the negative electrode active material for a secondary battery according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Powder for negative electrode of lithium ion secondary battery, and method of manufacturing the same

    JP2015153520A

  • Negative electrode material and nonaqueous electrolyte secondary battery

    CN110024188A

  • Silicon composite and method of manufacturing the same, negative electrode active material, and nonaqueous secondary battery

    JP2013234088A